english MENJADI MANUSIA DIANTARA YANG BUKAN MANUSIA: MENGIDENTIFIKASI SIMULACRUM DALAM THE LORD OF THE RINGS KARYA RR TOLKIEN - Hana Farida (Universitas Putera Batam, 2020)
Many different characters or races in The Lord of the Rings by JRR Tolkien had drawn many interest from critical readers. In this fantasy story of his, Tolkien utilized characters which were magical beings and ‘unrealistic’ such as elves, dwarves, wizards, hobbits, orcs, and trolls which were often identified as otherkins. On the other hand, he also presented humans who were ‘realistic’ characters familiar to the readers. This research was conducted in order to identify what is ‘real’ and what is ‘unreal’, and at the same time a ‘copy’ or a ‘fake’. The research was presented with a descriptive analytical method, and by assimilating the concept of simulacra by Jean Baudrilliard, it was argued that the line of real, unreal, fake, and copy was blurring. Humans were otherkins, and otherkins were humans.